2004
DOI: 10.1091/mbc.e04-06-0475
|View full text |Cite
|
Sign up to set email alerts
|

The Fusome Mediates Intercellular Endoplasmic Reticulum Connectivity inDrosophilaOvarian Cysts

Abstract: Drosophila ovarian cysts arise through a series of four synchronous incomplete mitotic divisions. After each round of mitosis, a membranous organelle, the fusome, grows along the cleavage furrow and the remnants of the mitotic spindle to connect all cystocytes in a cyst. The fusome is essential for the pattern and synchrony of the mitotic cyst divisions as well as oocyte differentiation. Using live cell imaging, greenfluorescent protein-tagged proteins, and photobleaching techniques, we demonstrate that fusoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 47 publications
4
77
0
Order By: Relevance
“…A general and extremely useful application of the collection is to identify new proteins that are associated with such structures and analyze the effect of mutations. For example, the preferential accumulation of Sec61 in the fusome observed here has been validated in recent studies (Snapp et al 2004). Proof of principle experiments of this type that focus on the fusome will be described elsewhere.…”
Section: Resultssupporting
confidence: 63%
“…A general and extremely useful application of the collection is to identify new proteins that are associated with such structures and analyze the effect of mutations. For example, the preferential accumulation of Sec61 in the fusome observed here has been validated in recent studies (Snapp et al 2004). Proof of principle experiments of this type that focus on the fusome will be described elsewhere.…”
Section: Resultssupporting
confidence: 63%
“…Only one integral membrane protein has been described in a recent study that localizes to fusomal membranes: the ER translocon channel protein Sec61␣. A GFP-fusion protein of Sec61␣ marks equally the fusome and all of the rough ER at some stages of cyst development in the germarium (Snapp et al, 2004). The same study showed that ectopic expression of a GFP-fusion protein of lysozyme with an engineered ER-retention signal (KDEL), LysGFP-KDEL, also localized to the fusome lumen in germaria.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, in germaria Mud is found strikingly colocalized with spectrosomes and the fusomes of region 1 ( Figure 10A). These structures are not only rich in cytoskeletal proteins like Hts (Lin et al 1994) but also rich in ER-derived membranes (McKearin 1997;Snapp et al 2004). Thus, their association with Mud could depend on its carboxy-terminal transmembrane-spanning domain.…”
Section: Infertility Of Mud Mutantsmentioning
confidence: 99%